Effect of short-term conservation temperature, with or without centrifugation, on the survival and motility of Catalonian donkey spermatozoa - Miró, Jordi; Taberner, Ester (Spanish Journal of Agricultural Research, 2020)
Aim of study: To analyze the effect of three short-term storage temperatures with or without removing seminal plasma on the survival and motility of donkey sperm and the response to refrigeration and centrifugation of the different spermatozoa subpopulations.Area of study: North-eastern Spain (Catalonia).Material and methods: Semen from seven Catalonian jackasses was diluted with a skimmed milk-based (Kenney) extender and different treatments were obtained: FRESH semen, FRESH semen immediately centrifuged to remove the seminal plasma before resuspension in Kenney extender (FRESH+CENTRIFUGATION), FRESH semen stored at 5/15/20ºC for 2 h (STORAGE 5/15/20ºC), and STORAGE 5/15/20ºC semen then centrifuged (STORAGE 5/15/20ºC+CENTRIFUGATION). Survival was examined using eosin-nigrosin stained smears. Motion was assessed by means of a computer-assisted sperm analyzer (CASA).Main results: The spermatozoa of the STORAGE 5ºC and 20ºC showed an overall motility similar to that seen in FRESH samples. However, the STORAGE 15ºC led to an important motility reduction. No differences were seen between the FRESH and STORAGE 5/15/20ºC with respect to progressive motility. However, STORAGE 5/15/20ºC+CENTRIFUGATION all reduced total motility, and STORAGE 15ºC+CENTRIFUGATION led to reduced survival. The sperm motile subpopulations structure of donkey semen was maintained after STORAGE 5/15/20ºC+CENTRIFUGATION, although STORAGE 15ºC+CENTRIFUGATION led to important changes. STORAGE 5/20ºC+CENTRIFUGATION, in contrast, only induced slight changes. STORAGE 20ºC+CENTRIFUGATION was associated with no change in the percentage of sperm cells belonging to each Subpopulation compared to FRESH sperm.Research highlights 2 h of storage at 20ºC followed by centrifugation is suitable for the short-term storage of donkey semen.